Kaji Eksperimental Pengunaan R22 dan R410A Berdasarkan Variasi Laku Aliran Massa Pada Mesin AC - Dian Wahyu -; Nasrullah - -; Khairul Amri - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
The development of the use of air conditioning machines (AC machines) is very high , due to the increased consumption of electricity for household needs are also increasing . Based on field observations of R22 refrigerant is still widely used in commercial air conditioning machines , where the refrigerant has properties that are not friendly to the environment . R410A refrigerant has been recommended to replace worn R22 . It became one of the rationale for conducting the assessment directly to efforts to reduce electricity consumption due to the use of air conditioning machines in the household and the efforts to preserve the environment . The research was conducted on a commercial air conditioning machines by testing the engine for both types of refrigerant ( R22 and R410A ) . Testing the engine characteristics , tested by varying the refrigerant mass flow rate for both refrigerants . The test results showed , electricity consumption ( compressor power ) for the use of both types of refrigerants is similar but uses R410A refrigerant produces a greater cooling effect than by using refrigerant R22 . In Overall effect of the variation of mass flow rate for both refrigerants clearly evident , the increase in mass flow rate causes enhancement of several variables such as the increase in compressor power , cooling effect , the effect of heat release , but for the coeficient of perfomance ( COP ) , the addition of the mass flow rate after COP The optimum value of the COP does not increase anymore . In this study, the highest COP values obtained in the refrigerant mass flow rate 3.4 g / s for R410A and R22 for 1.9 has the highest COP of 1.7 at a flow rate of refrigerant mass 3 g / s . For maximum cooling impact , generated by 0.502 kW to 0.572 kW usage for R22 and R410A.